2020
DOI: 10.48550/arxiv.2011.04321
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The clustering of critical points in the evolving cosmic web

Junsup Shim,
Sandrine Codis,
Christophe Pichon
et al.

Abstract: Focusing on both small separations and Baryonic Acoustic Oscillation scales, the cosmic evolution of the clustering properties of peak, void, wall and filament-type critical points is measured using two-point correlation functions in ΛCDM dark matter simulations as a function of their relative rarity. A qualitative comparison to the corresponding theory for Gaussian Random fields allows us to understand the following observed features: i) the appearance of an exclusion zone at small separation, whose size depe… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 58 publications
0
4
0
Order By: Relevance
“…Under the action of gravity, large-scale cosmic flows transport matter on large-scale cosmic structures from voids to sheets, and then via elongated filaments into clusters (Zel'Dovich 1970). The anisotropic large-scale matter distribution and its associated accretion processes have been investigated both theoretically and via N-body simulations (Pichon et al 2010;Codis et al 2015;Shim et al 2020) to establish a picture of the evolutionary and dynamical aspects of the cosmic network (see e.g. Hahn 2016 for a review).…”
Section: Introductionmentioning
confidence: 99%
“…Under the action of gravity, large-scale cosmic flows transport matter on large-scale cosmic structures from voids to sheets, and then via elongated filaments into clusters (Zel'Dovich 1970). The anisotropic large-scale matter distribution and its associated accretion processes have been investigated both theoretically and via N-body simulations (Pichon et al 2010;Codis et al 2015;Shim et al 2020) to establish a picture of the evolutionary and dynamical aspects of the cosmic network (see e.g. Hahn 2016 for a review).…”
Section: Introductionmentioning
confidence: 99%
“…Under the action of gravity, large-scale cosmic flows transport matter on cosmic large-scale structures from voids to sheets, and then via elongated filaments into clusters (Zel'Dovich 1970). The anisotropic large-scale matter distribution and its associated accretion processes have been investigated both theoretically and via N-body simulations (Pichon et al 2010;Codis et al 2015;Shim et al 2020), to establish a picture on the evolutionary and dynamical aspects of the cosmic network (see e.g. Hahn 2016, for a review).…”
Section: Introductionmentioning
confidence: 99%
“…The statistics of halo connectivity is expected to depend on the growth factor, and thus can constitute an new topological constraint on dark energy (Codis et al 2018), as the connectivity of halos must decrease with the cosmic time due to the Universe accelerated expansion which disconnects cosmic nodes from the network of filaments (Pichon et al 2010). More generally, the anisotropic environment of the cosmic web impacts the assembly bias of halos as theoretically explored by Musso et al (2018) who found that early-formed low-mass halos lie preferentially along filaments, while massive young ones are closer to the nodes (see also Shim et al 2020;Cadiou et al 2020). Cosmic web anisotropy is thus expected to be an indicator of halo assembly bias, and is therefore strongly correlated with halo properties (as discussed in Paranjape et al 2018;Ramakrishnan et al 2019).…”
Section: Introductionmentioning
confidence: 98%